As múltiplas faces da comodificação e a constituição da crítica acerca das práticas de consumo contemporâneas - Ceres Grehs Beck; Luis Henrique Hermínio Cunha (Ciências Sociais Unisinos)
The turn of “almost everything” to the quality of commodity reflects a contemporary process known as commodification (or commoditization). As this process promotes long-term impacts on the constitution of societies, it calls for a reflection on the sociological field of “what” can be bought and sold and about the role of legitimizing agents of these new markets that arise. After extensive review of the transdisciplinary academic literature, this paper summarizes the multiple forms of commodification in contemporary consumer practices. The examples involve tangible goods and symbolic aspects of daily life that become alienable, revealing how the culture, music, food, natural resources, places, violence, body parts, sex, traditions, education, religion and even emotions begin to have value in the market arena. The first purpose of this paper is to understand the origins of the concept, and then be able to seize the crucial features of the phenomenon in the dynamics of social change. It also aims at stimulating the debate and rethinking critically: In a world where “everything is for sale”, individuals also come to be treated as commodities? After the analysis of the cases, it is argued that commodifying processes change the ways of everyday life and affect the social relations, leading, ultimately, to reframe the “human qualities” and to the depoliticization of the individuals to the dynamics of social change.